Tinjauan Ekonomi Syariah Terhadap Strategi Pemberdayaan Ekonomi Masyarakat di MWC NU Dukun dan Panceng Gresik - Muhammad Syaikhul Fikry; Muhammad Lathoif Ghozali (ITB AAS INDONESIA Surakarta, 2022)
The high poverty rate and tends to increase is still a major problem faced by society in general. There are various ways to overcome these problems, one of which is empowerment. The Nahdaltul Ulama Representative Council (MWC NU) Dukun and Panceng are one of the institutions that have succeeded in making empowerment efforts to overcome economic problems in their respective regions. The purpose of this study was to examine the strategy of community economic empowerment carried out by MWC NU Dukun and Panceng. In addition, the application of sharia economics also needs to be analyzed to see whether the empowerment strategy carried out is in accordance with the existing sharia economic theory, considering that MWC NU is a socio-religious organization in the name of Islam. So, they should always be guided by the values that exist in Islam. This research uses qualitative research with a case study approach. Data collection techniques through observation, interviews, and documentation. Data analysis uses descriptive techniques to describe the nature or circumstances that are used as objects in the study, so as to produce descriptive data in the form of written words which are then concluded. The results showed that the application of sharia economics to community economic empowerment carried out by MWC NU Dukun and Panceng Gresik is in accordance with the existing sharia economic concept, namely in accordance with the goal of achieving falah and the purpose of upholding brotherhood and unity, and also in accordance with the principles of social security and the principle of mutual assistance.